2015
DOI: 10.1126/scisignal.aaa2155
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of single-cell cytokine secretion reveals a role for paracrine signaling in coordinating macrophage responses to TLR4 stimulation

Abstract: Cellular responses are mediated by heterogeneous intermediate signals that are secreted and sensed by the same cells. Cell-to-cell communication through these intermediate signals likely affects the collective response of cells within a population. We combined multiplexed, microwell-based measurements of cytokine secretion by single cells with data from the analysis of cell populations to determine the role of paracrine signaling in shaping the profile of inflammatory cytokines secreted by macrophages in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
158
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 132 publications
(171 citation statements)
references
References 61 publications
9
158
1
Order By: Relevance
“…This may suggest an important role for autocrine/paracrine type I interferon and other cytokine responses which could feedback on the TLR-activated macrophage to modulate the non-additive immune effector responses promoted by combined TLR activation (Xue et al, 2015). Such mediators likely also perform a key function in innate/adaptive immune cell communication through leukocyte recruitment and activation, as demonstrated by the selective functional annotation of the synergized gene clusters derived from ingenuity pathway analysis (IPA) (Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…This may suggest an important role for autocrine/paracrine type I interferon and other cytokine responses which could feedback on the TLR-activated macrophage to modulate the non-additive immune effector responses promoted by combined TLR activation (Xue et al, 2015). Such mediators likely also perform a key function in innate/adaptive immune cell communication through leukocyte recruitment and activation, as demonstrated by the selective functional annotation of the synergized gene clusters derived from ingenuity pathway analysis (IPA) (Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…Paracrine messengers secreted from cells that produce them in larger quantities can either trigger secretion of a secondary messenger from nonproducers and/or trigger responses in all the cells in the vicinity because of diffusive spread [49,50]. Thus, a paracrine messenger can be a shared messenger for a collective, coherent response.…”
Section: Crosstalk With Il-2 Signaling For Collective Scalingmentioning
confidence: 96%
“…We found that the total secretion of IL-6 and IL-10 was lower compared to conventional cultures, demonstrating that loss of paracrine signals attenuates inflammatory signaling (Fig. 2E; [46]). Heterogeneity of TNF secretion was especially high, with a few cells accounting for a majority of TNF secretion in the population.…”
Section: Imaging and Fluidics To Measure Nf-κb Pathway Signaling And mentioning
confidence: 98%